Robust sliding mode controller for buck DC converter in off-grid applications - Emad Awada; Eyad Radwan; Mutasim Nour (Bulletin of Electrical Engineering and Informatics, 2022)
This paper presents a robust sliding mode controller of DC-DC buck converter for renewable energy applications, such as photovoltaic systems in off-grid configurations. Photovoltaic systems in off-grid configuration are exposed to significant variations in input voltage and power loads. The proposed sliding mode controller presents a simple and efficient method of continuously updating the duty cycle of a pulse width modulation unit (PWM) of a buck converter. The PWM unit is operated at constant switching frequency of 10 kHz carrier signal and varying duty cycle. The differences in input voltage and power load are treated as two bounded uncertainties, thus eliminating the need for input voltage sensor and output current sensors leaving the system with a single sensor required to measure the converter output voltage. That is, measured output voltage is compared with the reference voltage to continuously update the average duty cycle value of PWM unit. Adjustment of PWM duty cycle is performed while maintaining the sliding condition always fulfilled. The simulation results of the proposed controller showed robustness and accuracy against power load fluctuation, changes in desired output voltage, and variations in the input supply voltage that may result from the varying level of irradiance and temperature.